Pengaruh Kecerdasan Emosional terhadap Prestasi Akademik pada Siswa SMK Kesehatan Prima Nusantara - Zakia Miftahul Faradisi; Diva Ingriani; Lidya Yuliani; Lisa Arista; Nurhasni Nurhasni; Tiara Tri Ariani; Zidan Maliki Akbar (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Academic achievement is the result of the learning process which can be measured using achievement tests such as exams and one of the factors so that students can achieve better learning achievement can be influenced by emotional intelligence. The aim of this research is to determine the effect of emotional intelligence on the academic achievement of Prima Nusantara Health Vocational School students. The sample of this research consisted of 93 students. Sampling was carried out by purposive sampling. The method used is quantitative, correlational research with linear regression. The emotional intelligence scale uses Goleman's theory modified by Aziz with a total of 25 items ranked from 1 to 4. Based on the results of a simple linear regression test, a sig value of 0.03 < 0.05 is obtained. so that the emotional intelligence variable influences the academic achievement variable.